Crystal structure, Hirshfeld surface analysis and computational study of the 1:2 co-crystal formed between N,N′-bis(pyridin-4-ylmethyl)ethanediamide and 4-chlorobenzoic acid - Tan, Sang Loon *; Tiekink, Edward R. T. * (international union of crystallography, 2020)
The asymmetric unit of the title 1:2 co-crystal, C14H14N4O22C7H5ClO2,comprises two half molecules of oxalamide (4LH2), as each is disposed about a centre of inversion, and two molecules of 4-chlorobenzoic acid (CBA), each in general positions. Each 4LH2 molecule has a (+)antiperiplanar conformation with the pyridin-4-yl residues lying to either side of the central, planar C2N2O2 chromophore with the dihedral angles between the respective central core and the pyridyl rings being 68.65 (3) and 86.25 (3), respectively, representing the major difference between the independent 4LH2 molecules. The anti conformation of the carbonyl groups enables the formation of intramolecular amide-N—HO(amide) hydrogen bonds, each completing an S(5) loop. The two independent CBA molecules are similar and exhibit C6/CO2 dihedral angles of 8.06 (10) and 17.24 (8), indicating twisted conformations. In the crystal, two independent, three-molecule aggregates are formed via carboxylic acid-O—HN(pyridyl) hydrogen bonding. These are connected into a supramolecular tape propagating parallel to [100] through amide-N—HO(amide) hydrogen bonding between the independent aggregates and ten-membered {HNC2O}2 synthons. The tapes assemble into a three-dimensional architecture through pyridyl- and methylene-C—HO(carbonyl) and CBA-C—HO(amide) interactions. As revealed by a more detailed analysis of the molecular packing by calculating the Hirshfeld surfaces and computational chemistry, are the presence of attractive and dispersive ClC O interactions which provide interaction energies approximately one-quarter of those provided by the amideN—HO(amide) hydrogen bonding sustaining the supramolecular tape.